India’s Role in the Restoration of Democracy in Maldives: Challenges and Options - Hemanta Kumar Biswas (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2022)
This article examines the dynamics of politics and international relations in South Asia with a reference to the Maldives. The Maldives is a small, fragile nation in South Asia, with 198 of its 1,192 islands inhabited. The peaceful Maldives, at the dawn of democracy, turned volatile when Nasheed started a campaign to impeach a criminal court judge. At that moment, India consciously did not want to get involved in the internal affairs of the Maldives. But in this opportunity, some countries like China, Pakistan, USA wanted to increase their influence in the democracy of Maldives. Some Islamic fundamentalist groups also tried to put a stain on the democracy of Maldives. A weak judiciary, corruption, and nepotism have taken a terrible toll on the country's democracy. In the presidential election of 2008 and 2013 Maldives, India's cooperation was an unprecedented event in this electoral system. However, Maldives has wandered between various ups and downs leading to the establishment of democracy. As a small country in South Asia, the establishment and context of democracy are very important, and Maldivian foreign policy towards India is always influenced by domestic politics. So, this paper focuses on the role of India to establish democracy in Maldives. The content analysis method was used in this study. Hence, this article contributes to studies of politics and international relations among countries in South Asia.